The Association Some Factors With Anxiety Postpartum in Semarang City - ita rahmaningtyas; Sri Winarni; Atik Mawarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat, 2019)
Some risks from health problems will be experienced by mothers who enter the puerperium. Based on data from Dinas Kesehatan Kota Semarang in 2018 there were 19 cases of maternal deaths in Semarang. Puskesmas with the highest maternal mortality cases were Puskesmas Tlogosari Wetan, Puskesmas Kedungmundu and Puskesmas Gayamsari where the puskesmas had the highest number of postpartum mothers in Semarang. In a preliminary study of 30 postpartum mothers who lived in all three Puskesmas working areas, 55% of postpartum mothers experienced anxiety during the puerperium. The population of the study was 162 postpartum mothers with 114 samples of postpartum mothers. The study design used a cross sectional study. Postpartum anxiety is measured using a modified Zung Self Rating Anxiety Scale questionnaire. This study aims to analyze several factors related to postpartum anxiety in Semarang. The results showed there was a relationship between the types of labor (p = 0.014), parity (p = 0.027), history of anemia during pregnancy (p = 0.012) with anxiety of postpartum mothers in Semarang. Multivariate analysis showed that the history of anemia during pregnancy (OR = 3,384; 95 % CI = 1,244 - 9,203) was the most dominant factor to influence the occurrence of anxiety postpartum. Mothers with cesarean delivery, parity of primiparous mothers and mothers with a history of anemia during pregnancy have a 58.6% probability to occur postpartum anxiety